Evaluation of clarity of presentation and applicability of monitoring instructions for patients using lithium in clinical practice guidelines for treatment of bipolar disorder. (13th August 2018) - Nederlof, M; Kupka, RW; Braam, AM; Egberts, ACG; Heerdink, ER
Abstract : Objectives: Clinical practice guidelines (CPGs) for treatment of bipolar disorder (BD) aim to provide guidance to health care professionals on monitoring of patients using lithium. The aim was to assess the clarity of presentation and applicability of monitoring instructions for patients using lithium in CPGs for treatment of BD. Methods: CPGs for treatment of BD were selected from acknowledged professional organizations from multiple continents. CPGs were rated on the clarity of presentation and applicability of lithium monitoring instructions using the Appraisal of Guidelines Research and Evaluation (AGREE) II tool. The applicability of monitoring instructions was assessed according to the Systematic Information for Monitoring (SIM) score. Monitoring instructions were considered applicable when a SIM score of ≥3 was found. Results: The clarity of presentation for six out of the nine CPGs was good (>70%) using the AGREE II tool. Only one CPG scored >70% on applicability. Descriptions of the resource implications and facilitators of and barriers to monitoring were most often missing. All CPGs contained instructions for monitoring of lithium serum levels and renal and thyroid function. Information provided in monitoring instructions (n = 247) was in general applicable to clinical practice (77%) based on the SIM score. Overall, a median SIM score of 3 (interquartile range 3‐4) was found. Conclusions: Improvement of the applicability of CPGs is recommended, and can be achieved by describing the resource implications and facilitators of and barriers to monitoring. In addition, information on critical values and instructions on how to respond to aberrant monitoring parameters are needed. With such improvements, CPGs may better aid health care professionals to monitor patients using lithium.